Field manual for rapid and non-destructive shoot biomass evaluations of staked yam - Iseki, K.; Matsumoto, R. (Japan International Research Center for Agricultural Sciences, 2021)
A rapid and easy method has been developed to evaluate the shoot biomass of staked yams. This method can reduce the time and cost required to evaluate shoot biomass when compared with destructive sampling methods. Using this new method, more than 200 accessions can be evaluated within 4 h, including the preparation time, while with the conventional methods of shoot sampling, oven drying, and weighing this process would take 3 days. In addition, owing to the non-destructive measurements of the normalized difference vegetation index (NDVI), evaluators can follow the growth of the same plant from planting to plant senescence. This reduces the size of the trial field required for plant replication during time-course of destructive sampling. The new method can be easily introduced into yam breeding programs worldwide. Additionally, no specialist knowledge is required to analyze the spectral reflectance data or record the NDVI value.